Medicinal plant research in Malaysia: scientific interests and advances - Ibrahim Jantan, (penerbit ukm, 2004)
This paper outlines the past five decades of scientific interests and advances in medicinal plant research in Malaysia. Initially the prime interest of research programmes has been on phytochemical studies leading to the discovery of biologically active compounds as chemical templates to produce new drug candidates. As the Malaysian herbal medicine market experiences an extraordinary growth, the research approaches taken have recently included activities to develop herbal medicines into quality, efficacious and safe products for human consumption. Advances in chromatographic and spectroscopic techniques have had a tremendous impact on the isolation and structure elucidation of the constituents of medicinal plants. The development of a series of bioassay methodologies and utilization of bioassay-guided isolation techniques have contributed significantly to the progress of medicinal plant research in Malaysia. Research work on some medicinal plants carried out by the local scientists will be illustrated as examples.